Locus of control, knowledge, attitude and practice for contraception among adolescents - Angela Ferreira da Silva; Maria Helena Baena de Moraes Lopes
ABSTRACT Objectives: to assess the relation of the locus of control with the adolescents' knowledge, attitude and practice (KAP). Methods: this is a cross-sectional study with 1,192 high school students. Data were collected using the KAP questionnaire and the Levenson locus of control scale and analyzed by descriptive statistics, Mann-Whitney U test and Kruskal-Wallis H test. Results: Women presented higher Externality Powerful Others locus of control than man (p=0.0015) and adolescents over 17, higher Externality Chance locus of control (p=<0.0001). Students who used contraceptive methods at the first contraceptive method had higher Externality Powerful Others (p=0.0107) and those who used coitus interruptus, had higher Externality Chance (p=0.0013). Internality was inversely proportional to the practice in relation to the dimensions of the locus of control. Conclusions: The dimensions of the locus of control were related to some contraceptive practices, but little or no relation to knowledge and attitude.